Storms - Busch, Miriam (Washington, D.C. : National Geographic, 2009)
Looks at all the big storms created by Mother Nature run amuk--from lightning and thunder to monsoons, hurricanes, and tornadoes. Features superlatives, jokes, and best of all, the incredible photographs available only from National Geographic.
Weather! -- Thunder and lightning -- Hail storm -- Tornado -- Sandstorm -- Blizzard -- Monsoon -- Hurricane -- Guess! -- A house for a storm -- Out of this world! -- Wacky weather -- Glossary.
Keywords: Storms -- Juvenile literature